What is an insect? = Que es un insecto? - Canizares, Susan, 1960-; Reid, Mary. (New York : Scholastic, 2003)
Uses simple text and photographs to explain what an insect is; compares various insects with creatures who are not.
"que es un insecto? Que no lo es? Abre este libro para saber!"--P. [4] of cover.
"Bilingual -- Bilingue"--Cover.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Text in English and Spanish.
Keywords: Insects -- Juvenile literature; Bilingual books; Spanish language materials -- Bilingual -- Juvenile literature